Antipyrine elimination as a dynamic test of hepatic functional integrity in obstructive jaundice. Issue 9 (September 1982) - McPherson, G A; Benjamin, I S; Boobis, A R; Brodie, M J; Hampden, C; Blumgart, L H
Abstract : Antipyrine elimination was studied in 29 patients with obstructive jaundice Antipyrine half-lives calculated using plasma concentrations at four and 24 hours ('short antipyrine test') were significantly correlated with those calculated using six time points (p less than 0.001). Mean antipyrine half-life was 28.3 +/- 8 hours (standard error) and was significantly longer than in normal subjects (p less than 0.001). Antipyrine half-life did not correlate with standard biochemical liver function tests, but correlated positively with the postoperative half-time for clearance of endogenous bilirubin (p less than 0.05), and negatively with hepatic cytochrome P-450 content measured in peroperative liver biopsies (p less than 0.05). Of six patients with antipyrine half-life greater than 20 hours, four died, one preoperatively of gastrointestinal haemorrhage and three postoperatively of sepsis. Serial short antipyrine tests were performed in 13 patients before and after biliary drainage. Those with an initial antipyrine half-life greater than 15 hours showed significant changes after drainage, while those with an antipyrine half-life less than 15 hours did not. The test of antipyrine half-life may aid in selecting high risk patients with obstructive jaundice for percutaneous biliary drainage before definitive surgery, and in determining the optimal time for such preliminary biliary decompression.